ANALISIS PEMERTAHANAN BAHASA SASAK TERHADAP PENGGUNAAN BAHASA ASING SEBAGAI MEDIA KOMUNIKASI DI KAWASAN EKONOMI KHUSUS MANDALIKA DESA PUJUT KABUPATEN LOMBOK TENGAH - Wahidah, Yulia Kurnia (Universitas Hamzanwadi, 2021)
The research took the population and sample in the Mandalika special economic area by taking focus of research on maintaining the use of the Sasak language as a medium of communication for people living in Mandalika area. Where, this research uses tapping method to get linguistic data that contains several variations. The data variations are distinguished based on three types, namely family realm, realm of friendship, and social realm. From these three domains, linguistic data were analyzed using the SPEAK technique from Dell Hymes. The aim was to find out the extent to which community in Mandalika special economic zone maintains when communicating using the Sasak language. Thus, the results of this research were, the used of the Sasak language was still very strongly used by the community in the family realm, the second Sasak language was also still maintained in the realm of friendship, while those that have begun to experience a shift was in the social realm. The shift that occurred in the social realm was due to the large number of tourists from various regions in Indonesia and even from outside of Indonesia State. Therefore, people when communicating they were used their second language such as Indonesian or foreign languages.Keywords: Sasak, Language Maintain; Communicative Method, Mandalika